Analysis of sexually transmitted infections in PrEP users: population assessment in Curitiba, Brazil - Roth, Maria Julia de Moraes Campos (2022)
Introduction: The pre-exposure prophylaxis (PrEP) is a globally recognized pharmacological approach, consisting of a daily dose of antiretroviral drugs usedto reduce the contamination rate by the human immunodeficiency virus (HIV). This combined prevention program was first offered by the Brazilian publichealth system in 2017 and was provided by Testing and Counseling Centers. Objective: To analyze the profile of pre-exposure prophylaxis users seen at Testingand Counseling Centers in Curitiba (state of Paraná, Brazil) and the presence of HIV and other sexually transmitted infections, such as syphilis, hepatitis Band C, in these users. Methods: This is an analytical, cross-sectional study, using database provided by the information system of the Testing and CounselingCenter. Results: Users of HIV pre-exposure prophylaxis are mostly young, white, single men, and who are part of the group of men who have sex withother men. It was verified that, even though the HIV pre-exposure prophylaxis plays a major role in HIV prevention, it is paramount to encourage combinedprevention, considering there is a significant relationship between the lack of barrier methods and positive results for syphilis. Conclusion: No connectionbetween the use of HIV pre-exposure prophylaxis and increased incidence of sexually transmitted infections was established in the present study